Evangelical gothic : the English novel and the religious war on virtue from Wesley to Dracula - Herbert, Christopher, 1941- (University of Virginia Press, 2019)
"Examining both the theology of John Wesley, George Whitefield, and William Wilberforce and novels by Charles Dickens, George Eliot, Sir Walter Scott, and Bram Stoker as well as a host of 'Evangelical novels' of the period, Herbert analyzes the Evangelical and anti-Evangelical forces at play in Victorian literature and culture, challenging accepted notions of the impact of the Evangelical movement on gothic Victorian literature."-- Provided by publisher.
Keywords: English fiction -- 19th century -- History and criticism.; Evangelicalism in literature.; Religious literature, English -- History and criticism.; Religion in literature.; Religion and literature -- England -- History -- 19th century.; Roman anglais -- 19e siècle -- Histoire et critique.; Évangélisme dans la littérature.; Littérature religieuse anglaise -- Histoire et critique.; Religion dans la littérature.; Religion et littérature -- Angleterre -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English fiction; Evangelicalism in literature; Religion and literature; Religion in literature; Religious literature, English; England; 1800-1899; Criticism, interpretation, etc.; History